The Belonging- Disjuncture Double Bind: Fragile Identities in Literary Works of East African Asians - Wangila, Makhakha Joseph (JOOUST, 2023)
The East African Asians have played a significant role in the political, social, economic as well as literary transformation of the region. Their long history and immense contribution in East Africa, has led to many scholarly works being written about them mainly focusing on the historical accounts and genealogy. However, emotions of fear and anxiety, which form a crucial motif in the literary experiences of East African Asians, have not been adequately captured. Using Bahadur Tejani’s Day After Tomorrow, Peter Nazareth’s In a Brown Mantle, M.G Vassanji’s The In-between World of Vikram Lall, Yusuf Dawood’s Eye of the Storm and Imam Verji’s Who Will Catch Us as We Fall, this study therefore analyzes the tropes of fear and anxiety in the literature of East African Asians as sampled from a group of twenty texts. This study focuses on the above authors because of their geographical location, thematic concerns raised through characterization and the period of production of their works, which highlights the transient nature of fear and anxiety. The main aim of this study is to explore the depiction of the discomfitures of identity and belongingness in the selected works of East African Asians. It interrogates the nexus between the history of East African Asians and their sense of identity as demonstrated in the selected texts. The study further examines the place of fear and anxiety in the quest for identity in the literature of East African Asians. It then examines how East African Asians negotiate their belonging and difference in their respective countries as depicted in the selected texts. This study uses both Psychoanalytic and postcolonial theories in engaging with the texts owing to the emotional issues of fear and anxiety that feature prominently in the selected texts as well as the historical experiences witnessed by the characters. The psychoanalysts focus on the fragmented image of the world and explore the alienated individual consciousness such as the interstitial position that the East African Asians find themselves in. Postcolonial theory draws attention to aspects of identity in relation to broader national histories. This research adopted an analytic research design which involves the identification of categories, themes and patterns from the primary texts to enable the researcher arrive at certain deductions. For instance, that history, serves to both alienate and give the Asians a sense of belonging to the East African region. It further concludes that fear and anxiety serve as unconscious mechanisms for the negotiation of Asian identity in the East Africa such that, to them, aspirations to a strong national identity must be firmly rooted in an authentic communal identity. Finally, the study concludes that the aspirations of Asians to attain a sense of belonging within the East African context is characterized by a feeling of ambivalence since t hey simultaneously nurture cosmopolitan visions as well as a desire for difference. The East African Asians encounter loss, fear, anxiety and nostalgia about their homeland when in the host countries which leads to their dislocated identity. They feel uhomely as a result of the cultural identity crisis encountered in the host country. The study therefore, contributes to the understanding of the role of fear and anxiety in identity formation process among the East African Asian communities.
Keywords: East African Asians